CFD SIMULATIONS OF LID DRIVEN CAVITY FLOW AT MODERATE REYNOLDS NUMBER - Omari, Reyad (European Scientific Journal, ESJ, 2013)
Computational fluid dynamics (CFD) simulations are carried out for laminar incompressible fluid flow in lid driven cavity (10 ≤ Re ≤ 1000). The ratio of the height to the width of the cavity are ranged over H/L = 0.5 to 1.5. A commercial finite volume package FLUENT was used to analyze and visualize the nature of the flow inside the cavity of different aspect ratio. The simulation results are presented in terms of velocity profile, pressure coefficient and stream contours. It was found that the pressure coefficient inside the cavity is strongly governed by the aspect ratio as well as the Reynolds number. Velocity profile for special case of a square cavity (AR = 1) was found to be in good agreement with previous experimental results. The present study has established that commercially-available software like FLUENT can provide a reasonable good solution of complicated flow structures including flow inside cavities.